The complete mitochondrial genome of Colias erate (Lepidoptera: pieridae). (1st November 2016) - Wu, Yunhe; Fang, Jie; Li, Wenbo; Han, Demin; Wang, Hui; Zhang, Baowei
Abstract: The complete mitochondrial genome of Colias erate was investigated and analyzed. The mitochondrial genome is a circular molecule of 15, 184 bp, containing 13 protein-coding genes (PCGs), two rRNA genes, 22 tRNA genes, and an A + T-rich region. The nucleotide composition of the C. erate mitogenome is strongly biased toward A + T nucleotides (81.34%). Nine protein-coding genes and 14 tRNA genes are encoded on the H strand, and the other four protein-coding genes and eight tRNA genes are encoded on the L strand. The arrangement of genes is identical to all know the Pieridae species. Finally, the phylogenetic relationships of 12 Pieridae species were reconstructed based on the nucleotide sequences of 13 mitochondrial PCGs using the Bayesian inference method. These molecular-based phylogenies support the traditional morphologically based view of relationships within the Pieridae.